Strength-training with whole-body vibration in long-distance runners: A Randomized trial - Bertuzzi, R.; Pasqua, L. A.; Bueno, S.; Damasceno, M. V.; Lima-Silva, A. E.; Bishop, D.; Tricoli, V. (International Journal of Sports Medicine, 2013)
A parallel group randomized trial was designed to analyze the impact of 6 weeks of strength training programs performed with or without whole-body vibration on muscular and endurance performance parameters in long-distance runners. 22 endurance runners were allocated into strength with whole-body vibration (n=8), without (n=8), and control (n=6) groups. Before and after the experimental period the subjects performed the following tests: a) maximum dynamic strength test, b) maximal incremental treadmill test, and c) time to exhaustion at velocity corresponding to maximal oxygen uptake. The fractions of the aerobic and anaerobic contribution in time to exhaustion test were also calculated. Both strength trained groups showed a similar increase in maximum dynamic strength (~18%). The aerobic contribution was enhanced for strength training group without whole-body vibration (~25%) after experimental period. No statistical differences were observed in any other variable. These results suggest that 6 weeks of strength training performed with or without whole-body vibration improve similarly the maximum dynamic strength in long-distance runners. In addition, both training modes studied had no deleterious effects on the traditional parameters of endurance performance, traditional strength training program results in increased aerobic contribution during high-intensity aerobic exercise